Application of NF Polymeric Membranes for Removal of Multicomponent Heat-Stable Salts (HSS) Ions from Methyl Diethanolamine (MDEA) Solutions - Asma Ghorbani; Behrouz Bayati; Teresa Poerio; Pietro Argurio; Tavan Kikhavani; Marzieh Namdari; Licínio M. Ferreira (Molecules, 2020)
This study presents an efficient and scalable process for removing the heat-stable salts (HSS) ions from amine solution while recovering methyl diethanolamine (MDEA) solution for its reuse in gas sweetening plants. The presence of HSS in the amine solution causes the loss of solvent capacity, foaming, fouling, and corrosion in gas sweetening units so their removal is crucial for a more well-performing process. Furthermore, the recovery of the amine solution can make the sweetening step a more sustainable process. In this study, for the first time, the removal of a multicomponent mixture of HSS from MDEA solution was investigated via a nanofiltration process using flat-sheet NF-3 membranes. The impact of operating parameters on salts and amine rejection, and flux, including the operating pressure, HSS ions concentration, and MDEA concentration in the feed solution was investigated. Results based on the nanofiltration of an amine stream with the same composition (45 wt.% MDEA solution) as that circulating in a local gas refinery (Ilam Gas refinery), demonstrated a removal efficiency of HSS ions in the range from 75 to 80% and a MDEA rejection of 0% indicating the possibility of reusing this stream in the new step of gas sweetening.